Aproximación del efecto financiero de la sección 17 de las NIIF para pymes en el sector industrial con respecto a la última actualización del 2015 - Díaz Jurado, John Mario (Universidad Antonio Nariño, 2021)
Considering that section 17 is one of the most important items in this sector due to the large participation within the organization, it's used as reference to do an reflexive article where you can find information of papers in this area and the impact of section 17 itself, thus, it takes into account the changes of the last actualization and information of other educational documents in order to reach a conclusion of his positive and negative impact in financial information. First, the main focus on which this topic will be addressed is the property, plant and equipment especially the fixed assets (machinery) in some companies of the industrial sector, in which section 17 have been already applied and changes in measurements have been considered.